Sociodemographic and health profile of asylum-seekers in Rio de Janeiro, 2016-2017 - João Roberto Cavalcante; Raquel Proença; Ignacio Cano; Anete Trajman; Eduardo Faerstein (Universidade de São Paulo, 2022)
ABSTRACT OBJECTIVE To analyze the sociodemographic profile and self-reported health conditions of asylum-seekers in Rio de Janeiro. METHODS A cross-sectional study of secondary data, collected from asylum claims forms completed in 2016 and 2017, at Cáritas Arquidiocesana do Rio de Janeiro (Cáritas-RJ). Descriptive analyses were performed and absolute and relative frequencies and 95% confidence intervals were calculated. RESULTS Claims completed by 818 asylum-seekers from 49 different countries were identified, of whom 126 (20.3%) were stateless, 510 (62.7%) were male, 797 (97.4%) were adults, with a mean age of 30.5 years, 551 (73.5%) were single, 340 (44.1%) had higher education, and 27 (4.0%) were unemployed in their country of origin before coming to Brazil. Fear of persecution for political opinion, violation of human rights, and risk of torture stood out among the reasons stated for requesting asylum. To reach Brazil, 629 (80.5%) traveled only by plane. Regarding health conditions, 216 (29.0%) reported having some symptom, disease or health problem, the most frequent being pain, vision problems, infectious diseases (including HIV/AIDS), and hypertension. Only 15 individuals (2.2%) reported being in some medical or psychological treatment; 42 (6.0%) reported visual impairments, 14 (2.0%) reported physical impairments and 4 (0.6%) hearing impairments. CONCLUSIONS Unlike other countries, where forced migrants with a low level of education enter clandestinely by sea or land, asylum-seekers residing in Rio de Janeiro between 2016 and 2017 were mostly adults with higher education who migrated using air transport. They had primary care-sensitive health conditions that could be treated via access to public primary health care services.